1965
DOI: 10.1071/ar9650014
|View full text |Cite
|
Sign up to set email alerts
|

Extension growth of grass tillers in the field

Abstract: Growth-recording instruments were used to measure extension growth of grass tillers under a variety of outdoor conditions. Variation in the rate of extension growth between tillers was fairly high, but nevertheless was found to be highly correlated with field temperature while only poorly correlated with light energy. By using these instruments, estimates of growth activity can be made rapidly and over relatively short periods of time; and it is suggested that the method may have use in assessing species for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Although it is generally agreed that radiation is much less important than temperature in determining leaf extension rate (Weihing, 1963;Thomas, 1975), it is difficult to escape the conclusion that the two may have interacted in this situation. Some such links have been shown (Williams and Biddiscombe, 1965;Thomas and Norris, 1977;Norris, 1985).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although it is generally agreed that radiation is much less important than temperature in determining leaf extension rate (Weihing, 1963;Thomas, 1975), it is difficult to escape the conclusion that the two may have interacted in this situation. Some such links have been shown (Williams and Biddiscombe, 1965;Thomas and Norris, 1977;Norris, 1985).…”
Section: Discussionmentioning
confidence: 91%
“…Rates of leaf extension have been shown to be influenced by temperature (Williams and Biddiscombe, 1965;Peacock, 1971). Peacock (1975b) established that temperature is effective at the level ofthe stem apex which in perennial ryegrass is located close to the soil surface during the vegetative and early reproductive phases of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the leaf of the tea plant, catechin is reported to be formed in the chloroplasts and to accumulate in vacuoles of the palisade parenchyma (catechin completely absent from the leaf epid e r m i~) .~ Also in the tea plant, flavone glycosides are reported to be more characteristic of older leaves rather than young leaves; these phenolics could not be found elsewhere in the plant.1° In the leaves of succulent plants, flavonol 3-glycosides have been found only in the epidermis.l' The leaf laminae of the tobacco plant has been found to contain more phenolics than the stem, leaf midrib, pith and root.12 Isochlorogenic acid, although a regular leaf constituent of Pyrus, could not be detected in the leaf of Malus; in this genus isochlorogenic acid could be detected only in the blossom petals. 13 In bamboo shoots p-coumaric acid is reported to increase drastically in content from the top towards the lower parts of bamboo shoots, whereas ferulic acid did not increase so markedly ; interestingly, cinnamic acid hydroxylase activity was also found to increase in a similar manner.14 It has been reported that in the tea plant high concentrations of catechins, flavonols and depsides are restricted to the young vegetative and floral shoots whereas leucoanthocyanidins are characteristic of the more bulky axial tissues of the plant.1° In the Sunflower plant, concentration gradients of caffeoylquinic acids have been found in the stems; this is considered to bear some possible relationship to 1ignifi~ation.l~ These findings, and also the findings reported in the present paper, would seem to indicate that at least some plant phenols are somehow involved in physiological function; the exact nature of this function remains unknown but some involvement in the storage of food reserves, growth regulation and the control of lignification remain as widely canvassed possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous measurements of the lengths of shoots and leaves (Figs. 2, 3, 4, 5, and 7) were made using growth recorders adapted from hygrothermographs as in Williams and Biddiscombe (1965). Each recorder provided a graph of cumulative change in height (magnified two to four times) against time (7 days/chart) at two points, e.g.…”
Section: Methodsmentioning
confidence: 99%